Internationalization of higher education via distance learning: A grounded theory study in Turkey - Ergin, Hakan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2017., 2017)
This qualitative study examined how a faculty in Turkey internationalized via distance learning. This was made by multiple data collection and analysis procedures. First, observations were made to explore the operation of the faculty. Second, official documents produced by the faculty, university, national and supranational organizations were analyzed to reveal how hierarchical relations among policymakers influenced the faculty's approach to internationalization. Third, semi-structured interviews were conducted with 10 administrators of the faculty, 10 faculty members and 10 international distance students to explore their experiences in international distance learning programs. Based on the findings, the operation of the faculty was associated with the theory of the industrialization of teaching (Peters, 1983). Next, it was explored that the faculty administration was under the pressure of the massification of higher education and world university rankings. It was revealed that the participants had undergone academic, economic, social/cultural and psychological transformative influences of international distance learning programs. The main contribution of this study to the literature is that a theoretical model of distance internationalization has been proposed. The model introduces the rationales, philosophical foundations, global pressure, advantages, challenges and transformative influences in the internationalization of higher education via distance learning. It is expected to provide a route map for policymakers and higher education institutions with an agenda of internationalization via distance learning.
Keywords: Education, Higher -- Effect of technological innovations on.; Internet in higher education.; Education, Higher -- Computer-assisted instruction.; Distance education -- Turkey.